The Influence Of Incentives And Work Environment On Performance Miss Cimory Pt Cisarua Mountain Dairy Lampung : Miss Cimory Center West Metro Case Study - Komang Aris Wijaya; Hendri Dunan (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this research is to determine the effect of incentives and work environment on performance Employee. This research was conducted at PT. Cisarua Mountain Dairy Lampung, case study at Miss Cimory Metro Barat. The type of research data used is quantitative. The data analysis method used in this research is multiple linear regression which is used to determine the influence of incentives and work environment on employee performance at the West Metro Center, by distributing questionnaires via Google Form to all 34 employees. Testing the research hypothesis uses SPPS Version 20. The results of this research show that incentives have no partial effect (p>0.05) on performance. Then the Work Environment has a significant (p<0.05) partial effect on Performance. Incentives and Work Environment simultaneously have a significant (p<0.05) effect on Employee Performance. It is recommended that management pay attention to incentives and work environment so that they can influence employee performance at the Miss Cimory Center in Metro Barat, Lampung.